Rapid discrimination of colon cancer cells with single base mutation in KRAS gene segment using laser tweezers Raman spectroscopy. Issue 3 (26th December 2018) - Liu, Mengmeng; Liu, Xiujie; Huang, Zufang; Tang, Xiaoqiong; Lin, Xueliang; Xu, Yunchao; Chen, Guannan; Kwok, Hang Fai; Lin, Yao; Feng, Shangyuan
Abstract : Laser tweezers Raman spectroscopy (LTRS) as a label‐free and noninvasive technology has been proven to be an ideal tool for analysis of single living cells, which provides important fingerprint information without interference from surrounding environments. For the first time, LTRS system was successfully used to examine the colon cancer cells with single base mutation in KRAS gene segment, including DKS‐8 (KRAS wild‐type [WT]) and DLD‐1 (KRAS mutant‐type [MT]), HKE‐3 (KRAS WT) and HCT‐116 (KRAS MT). Spectra changes of some vital biomolecules due to the gene mutation state were sensitively recorded by our home‐made LTRS system. As a result of the comparison between DKS‐8 and DLD‐1 cells, an index of 97.5% of correct classification was obtained by combining LTRS with principle component analysis coupled with linear discriminant analysis (PCA‐LDA) statistical analysis, while an index of 97.0% of correct classification was achieved between HKE‐3 and HCT‐116 cells. Moreover, between WT cells (DKS‐8 and HKE‐3) vs MT cells (DLD‐1 and HCT‐116), the index of correct classification was 81.2%, which was quite encouraging. Our preliminary results showed that the LTRS system coupled with PCA‐LDA analysis will have a great potential for further applications in the rapid and label‐free detection of circulating tumor cells in liquid biopsy. Abstract : Laser tweezers Raman spectroscopy (LTRS) as a label‐free and noninvasive technology was used to examine the colon cancer cells with single base mutation in KRAS gene segment for the first time. As a result of statistical analysis, a high correct classification was achieved. Our preliminary results showed that the LTRS system has great potential for further applications in the rapid and label‐free detection of circulating tumor cells in liquid biopsy.